Administrasi Ketatausahaan di Madrasah Aliyah Negeri (MAN) Kota Kupang: - aliumar, ali (Widyadewata, 2024)
This study aims to determine the role of Administrative Administration in Madrasah Aliyah Negeri (MAN) Kupang City. This type of research is field research using qualitative descriptive research methods. The research took place at MAN Kupang City with the research subjects being the principal, 15 administrative employees. Data collection techniques used are interviews, observation, and documentation. The results show that administrative administration has a very important role in managing madrasa performance, where all activities are carried out jointly by administrative staff and school principals, starting from the planning, implementation, and evaluation stages as well as the division of roles, duties and responsibilities. each each. Administration is an important part in the madrasa to support the performance and fulfillment of the madrasa. For example, the role of administration is to provide information to the head of Madrasah. With this information, the Head of Madrasah in considering his decision will be more appropriate, because the task of the administration itself is to collect, record, manage, send and store documents that are considered important for the madrasa. And one of the benefits of having madrasa administration is madrasa work and preventing possible mistakes in work.